Transcriptomics and metabolomics profiling of Paris polyphylla var. yunnanensis with different growth years - Xiaoye Zhang; Jia Chen; Ping Xu; Xuan Zhang; Shuiyi Yang; Jie Zhang; Xiheng Wan; Yingsi Gao; Guowei Zheng (Scientific Data)
Abstract Paris polyphylla var. yunnanensis is a widely cultivated rhizomatous perennial woody plant known for producing highly valued steroidal saponins. Steroidal saponins serve as the primary active components and exhibit a variety of pharmacological effects. Their production is closely correlated with the growth environment and developmental stages of P. polyphylla. However, the medicinal value of P. polyphylla cultivated for varying durations remains unclear. In this study, we collected samples of P. polyphylla aged 3 to 8 years for metabolome and transcriptome sequencing analysis. The total saponin content was found to be significantly higher in 8-year-old P. polyphylla compared to younger plants. A total of 1,510 metabolites and 270.65 Gb of clean data were identified from these samples. This study provides insights into the medicinal values of P. polyphylla at different growth stages and elucidates the metabolic pathways for specific steroidal saponins.